If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(n + 3) + -7(-8n + 5) = -29 Reorder the terms: 2(3 + n) + -7(-8n + 5) = -29 (3 * 2 + n * 2) + -7(-8n + 5) = -29 (6 + 2n) + -7(-8n + 5) = -29 Reorder the terms: 6 + 2n + -7(5 + -8n) = -29 6 + 2n + (5 * -7 + -8n * -7) = -29 6 + 2n + (-35 + 56n) = -29 Reorder the terms: 6 + -35 + 2n + 56n = -29 Combine like terms: 6 + -35 = -29 -29 + 2n + 56n = -29 Combine like terms: 2n + 56n = 58n -29 + 58n = -29 Add '29' to each side of the equation. -29 + 29 + 58n = -29 + 29 Combine like terms: -29 + 29 = 0 0 + 58n = -29 + 29 58n = -29 + 29 Combine like terms: -29 + 29 = 0 58n = 0 Solving 58n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Divide each side by '58'. n = 0 Simplifying n = 0
| 30-x=3+6x | | 6cm+8cm=w | | 4x=8-3x | | 15+7=4a | | f(a)=9(-3)-5 | | 6x-15=15+9x | | 2x-=-25 | | 11x-4=2x-3 | | 5w+(w*w)-(4*9)=0 | | 3*s-6+2=4*s+2-21 | | 9x--5=6 | | 14x+6x-10=90 | | -x^2+2*x=-6 | | 3(0)-3y=9 | | 2xy=3h | | x+8=8-4x | | 11x-9-10x=-9 | | -3(7-6r)= | | 4b+12+2b=46 | | 5s+4s+15=-56 | | 3x^2-16x-35=03 | | 5(3x-2)=2(3x+5) | | 9y+3x=18 | | 48=-2-12x | | 17=5(-7-4k)+4(1+8k) | | -4x-bx= | | -339=8(4+7v)-3v | | -117=-9h | | 0.3j+1.8=0.4(j+5)-0.2 | | 3.6r=43.2 | | 33x-10=7x+3 | | 17=5(-7-4k)+4(1+8x) |